2022
DOI: 10.1039/d1dt03875c
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between mitochondria-damaging platinum(iv) prodrugs and cytochrome c

Abstract: In this work, we present the first study about the interactions of mitochondria-damaging Pt(IV) prodrugs with cytochrome c. We synthesized a cisplatin-based Pt(IV) prodrug bearing a lipophilic hydrocarbon tail and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Амфифильная структура противоопухолевых агентов способствует его накоплению в митохондриях раковых клеток [17], что вызывает накопление окислительных нуклеиновых кислот в цитоплазме [18]. Опухолевая агрессия увеличивает продукцию митохондриальных АФК, ПОЛ, снижая потенциал митохондриальной мембраны [19].…”
Section: оригинальные исследованияunclassified
“…Амфифильная структура противоопухолевых агентов способствует его накоплению в митохондриях раковых клеток [17], что вызывает накопление окислительных нуклеиновых кислот в цитоплазме [18]. Опухолевая агрессия увеличивает продукцию митохондриальных АФК, ПОЛ, снижая потенциал митохондриальной мембраны [19].…”
Section: оригинальные исследованияunclassified
“…Previous studies have demonstrated that lipophilic Pt(IV) prodrugs with hydrocarbon tails possess high potency and promising pharmacokinetics. [28][29][30][31][32][33][34][35][36] Our recent research has also shown that such prodrugs can utilize CD36 upregulation to effectively target ovarian cancer cells. 8 In this new project, we have modified the Pt(IV) prodrug by attaching a fluorescein moiety, which enables photoactivation upon 490 nm irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…24 The nucleophilic hydroxido ligands in platinum(IV) complexes can react with common organic electrophiles, including acid chloride, acid anhydride, NHS-esters, and isocyanates, to form well-designed platinum(IV) prodrugs. [25][26][27][28][29][30][31][32][33][34] Additionally, direct esterification of hydroxido ligands with carboxylic acids can occur with the assistance of coupling reagents. [35][36][37][38][39][40] Moreover, axial halogen ligands or an acetamidato ligand can be introduced by utilizing halogenation reagents (F•py, NCS, and NBS) in water or H 2 O 2 in mixed solvents (MeCN and MeOH); however, to further functionalize these asymmetric platinum(IV) complexes, the remaining axial hydroxido ligand must participate.…”
Section: Introductionmentioning
confidence: 99%